EFFECT OF WORK MOTIVATION AND WORK DISCIPLINE ON EMPLOYEE PERFORMANCE OF PT. BIO CYCLE INDO TAPUNG - Syukri Makmur; Zamhir Basem; Muhammad Yusril (Jurnal Riset Manajemen Indonesia, 2022)
This study aims to analyze and describe the effect of work motivation and work discipline simultaneously and partially on the performance of employees of PT. Bio Cycle Indo in Tapung District. This study uses multiple linear regression analysis with a sample of 80 employees. Based on the results of the study, there is a significant relationship between work motivation and work discipline, either simultaneously or partially on employee performance. Work motivation and work discipline have an effect on employee performance by 66.0%. While the remaining 32.0% is influenced or explained by other variables that are not included in this research model.